2014
DOI: 10.1155/2014/854824
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-ResistantStaphylococcus aureusProstatic Abscess in a Liver Transplant Recipient

Abstract: Prostatic abscesses are usually related to gram-negative bacilli. However, methicillin-resistant Staphylococcus aureus (MRSA) has emerged as a substantial cause of prostatic abscesses in recent years. Herein, we report the case of a 31-year-old man with a history of orthotopic liver transplantation 10 years ago who presented with acute onset dysuria and abdominal pain and was diagnosed with a MRSA prostatic abscess. To our knowledge, this is the first case describing a prostatic abscess in a liver transplant r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…In the 1970s, approximately 75% of these infections were susceptible to first‐generation antibiotics; now, only approximately 20% are susceptible . S. aureus remains the most common hematogenously spread infection leading to PA. Increasing cases as a result of MRSA, both nosocomial and community‐acquired, are a growing concern, with >30 cases of PA as a result of S. aureus (methicillin‐resistant and ‐sensitive) reported in the literature . Other reported bacterial pathogens include Klebsiella pneumoniae , Enterococcus species, Streptococcus species, Pseudomonas aeruginosa , Bukholderia pseudomallei and Brucella melitensis .…”
Section: Causative Organismsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 1970s, approximately 75% of these infections were susceptible to first‐generation antibiotics; now, only approximately 20% are susceptible . S. aureus remains the most common hematogenously spread infection leading to PA. Increasing cases as a result of MRSA, both nosocomial and community‐acquired, are a growing concern, with >30 cases of PA as a result of S. aureus (methicillin‐resistant and ‐sensitive) reported in the literature . Other reported bacterial pathogens include Klebsiella pneumoniae , Enterococcus species, Streptococcus species, Pseudomonas aeruginosa , Bukholderia pseudomallei and Brucella melitensis .…”
Section: Causative Organismsmentioning
confidence: 99%
“…20 S. aureus remains the most common hematogenously spread infection leading to PA. Increasing cases as a result of MRSA, both nosocomial and community-acquired, [35][36][37] are a growing concern, with >30 cases of PA as a result of S. aureus (methicillin-resistant and -sensitive) reported in the literature. 38 Other reported bacterial pathogens include Klebsiella pneumoniae, [39][40][41] Enterococcus species, 34,42,43 Streptococcus species, 44 Pseudomonas aeruginosa, 45 Bukholderia pseudomallei [46][47][48] and Brucella melitensis. 49 Atypical organisms are seen more frequently in the severely immunocompromised, such as post-transplant and AIDS patients, 18 and include pathogens seen at a higher incidence in those populations, such as mycobacteria (Mycobacterium avium intracellulare, mTB 50,51 ), as well as pathogenic fungi, such as Coccidioides immitis, 52 Candida species, [53][54][55] Cryptococcus neoformans, 20,56 Blastomyces dermatitidis, 57 Histoplasma capsulatum 58,59 and Cladophialophora carrionii.…”
Section: Causative Organismsmentioning
confidence: 99%
“…Of the gram-negatives, the most common is Escherichia coli with 75% of isolates susceptible to first-line antibiotics in the 1990s but only 22% in the 2000s [5]. Recently, there have been increasing numbers of case reports detailing incidences of both methicillin-sensitive and resistant S. aureus, with 33 cases reported in the literature as of 2014 [10]. Other reported bacterial pathogens include Klebsiella pneumoniae, Pseudomonas aeruginosa, Enterococcus species, Streptococcus species, and Burkholderia pseudomallei [2,5].…”
Section: Discussionmentioning
confidence: 99%
“…There are no clear guidelines regarding management of PA [ 6 ]. In a retrospective study, antibiotic therapy for 2 weeks was suggested for patients with a PA <2 cm in size, minimal symptoms and no leukocytosis [ 9 ]. Transperineal aspiration was recommended if the above criteria were not met and if there was a persistent abscess [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study, antibiotic therapy for 2 weeks was suggested for patients with a PA <2 cm in size, minimal symptoms and no leukocytosis [ 9 ]. Transperineal aspiration was recommended if the above criteria were not met and if there was a persistent abscess [ 9 ]. Out of 26 MRSA PA cases 22 cases were treated by drainage and antibiotic therapy and only 4 cases were treated by antibiotic therapy alone [ 2 ].…”
Section: Discussionmentioning
confidence: 99%